Structural and local physical properties of relaxor ferroelectric thin films - Melo, Michael de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Polycrystalline thin films of Pb0.91La0.09Zr0.65Ti0.35O3 (PLZT9/65/35) and Sr0.75Ba0.25Nb2O6 (SBN75) were prepared by the chemical polymeric routine in order to investigate their physical properties at the macro- and nanoscale. X-ray diffraction (XRD), piezoresponse force microscopy (PFM), and scanning electron microscopy (SEM) were used as investigative tools. PLZT9/65/35 and SBN75 thin films have exhibited perovskite and tungsten bronze crystal structure at room temperature, as it was expected in this nominal composition for these relaxor ferroelectric materials. In addition, Rietveld method of the crystalline structure has revealed the thickness dependence of the crystallite size, grain size, and microstrain. The transition temperature of SBN thin film showed to shift to lower temperatures, suggesting the presence of a higher defect concentration, such as oxygen vacancies, chemical disorder, and lattice defects in this film. SEM has exhibited the porosity features in both thin films and has confirmed the existence of chemical elements (such as oxygen, niobium, lanthanum, strontium, platinum, silicon and barium) in film surface and near the substrate. Ferroelectric properties have been investigated by PFM and the results have suggested a thickness and crystallite size dependence of the piezoelectric response. Also in this work, the dynamic of ferroelectric domain switching and the induced domain relaxation were studied using the switching spectroscopy PFM (SS-PFM) in both relaxor systems as a function of variable DC applied voltages and pulse durations.

Filmes policristalinos de Pb0,91La0,09Zr0,65Ti0,35O3 (PLZT9/65/35) e de Sr0,75Ba0,25Nb2O6 (SBN75) foram preparados por uma rotina química polimérica para investigarmos as suas propriedades em nano- e macroescala. Difração de raios-X (DRX), microscopia de força atômica de piezoresposta (PFM), e microscopia eletrônica de varredura (SEM), foram utilizados como ferramentas investigativas. Os filmes finos de PLZT9/65/35 e de SBN75 exibiram estrutura peroviskita e tungstênio bronze, respectivamente, conforme esperado à temperatura ambiente e na composição nominal para estes materiais ferroelétricos relaxores. Além disso, o refinamento de Rietveld da estrutura revelou a dependência do tamanho do cristalito e do microstrain com a espessura. A temperatura de transição de fase do filme de SBN mostrou um deslocamento para valores menores de temperatura, sugerindo a presença de concentração de defeitos, tais como vacâncias de oxigênio, desordem química e defeitos de rede, maior no filme de SBN. Microscopia eletrônica de varredura (SEM) exibiu o caráter poroso de ambos os filmes. Propriedades ferroelétricas desses filmes foram investigados por meio da técnica de PFM. A piezoresposta mostrou ter uma dependência em função do tamanho do cristalito e da espessura. Neste trabalho, a dinâmica de reversão de domínios ferroelétricos e a relaxação de domínios induzidos foram estudados por meio do uso da espectroscopia de chaveamento (SS-PFM) em ambos os sistemas em função da tensão DC e do tempo de duração do pulso.
Propriedades físicas e estruturais de filmes finos ferroelétricos relaxores
Keywords: Thin films; Relaxors; Piezoresponse Force Microscopy (PFM); Filmes finos; Relaxores; Microscopia de Força Atômica de Piezoresposta (PFM)